IMPLEMENTASI NILAI-NILAI DAKWAH DALAM QS FUSHILAT AYAT-33 DI ERA DIGITAL - Mastori; Asep Maskur; Zenal Arifin (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
Surah Fushilat verse 33 provides basic guidelines for da'wah activities with an emphasis on the importance of serving goodness, faith in Allah, and good deeds as the basis of Islamic communication. In today's digital era, da'wah has undergone a significant transformation through the use of information technology and social media as the main means. This study aims to analyze how the values ​​contained in QS Fushilat verse 33 can be implemented in da'wah in the digital era. The study used a qualitative approach with thematic interpretation method, connecting the message of the Qur'an with modern da'wah practices. The results of the study show that the main values ​​in da'wah such as truth, wisdom, and patience remain relevant and serve as guidelines in facing the challenges of digital da'wah, such as the rise of disinformation, lack of religious literacy, and social polarization. Optimal implementation requires mastery of technology, presentation of interesting content, and management of friendly interactions on digital platforms.